2006
DOI: 10.1007/s00464-005-0589-4
|View full text |Cite
|
Sign up to set email alerts
|

Preoperative esophageal manometry and outcome of laparoscopic adjustable silicone gastric banding

Abstract: Preoperative esophageal manometry does not predict weight loss or GERD outcomes after LASGB in morbidly obese patients. Postoperative emesis was more common in patients with abnormal manometry findings, but such symptoms were manageable and did not lead to poor weight loss or to band removal or increased band-related complications.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
20
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
5
5

Relationship

1
9

Authors

Journals

citations
Cited by 34 publications
(21 citation statements)
references
References 27 publications
(26 reference statements)
1
20
0
Order By: Relevance
“…Lew et al [19] found a 4-mm increase in esophageal diameter after 6 months and another 4-mm increase after 12 months. However, the percentage of patients without dilation was not given.…”
Section: Discussionmentioning
confidence: 97%
“…Lew et al [19] found a 4-mm increase in esophageal diameter after 6 months and another 4-mm increase after 12 months. However, the percentage of patients without dilation was not given.…”
Section: Discussionmentioning
confidence: 97%
“…A standard 5-trocar pars flaccida technique was used to place the adjustable gastric band, as described previously [6]. The first two follow-ups were scheduled at 2 at 6 weeks and thereafter patients returned monthly for the first year and then every 6 months thereafter.…”
Section: Methodsmentioning
confidence: 99%
“…In a previous article [2], we described our experience with performing esophageal manometry before the placement of an adjustable gastric banding. Of 77 patients with preoperative manometry, 14 were found to have esophageal dysmotility, mostly decreased lower esophageal sphincter tone.…”
mentioning
confidence: 99%